Biogenesis of Type V pili. (9th September 2020) - Shoji, Mikio; Shibata, Satoshi; Sueyoshi, Takayuki; Naito, Mariko; Nakayama, Koji
Abstract: Pili or fimbriae, which are filamentous structures present on the surface of bacteria, were purified from a periodontal pathogen, Porphyromonas gingivalis, in 1980s. The protein component of pili (stalk pilin), which is its major component, was named FimA; it has a molecular weight of approximately 41 kDa. Because the molecular weight of the pilin from P. gingivalis is twice that of pilins from other bacterial pili, the P. gingivalis Fim pili were suggested to be formed via a novel mechanism. In earlier studies, we reported that the FimA pilin is secreted on the cell surface as a lipoprotein precursor, and the subsequent N‐terminal processing of the FimA precursor by arginine‐specific proteases is necessary for Fim pili formation. The crystal structures of FimA and its related proteins were determined recently, which show that Fim pili are formed by a protease‐mediated strand‐exchange mechanism. The most recent study conducted by us, wherein we performed cryoelectron microscopy of the pilus structure, provided evidence in support of this mechanism. As the P. gingivalis Fim pili are formed through novel transport and assembly mechanisms, such pili are now designated as Type V pili. Surface lipoproteins, including the anchor pilin FimB of Fim pili that are present on the outer membrane, have been detected in certain Gram‐negative bacteria. Here, we describe the assembly mechanisms of pili, including those of Type V and other pili, as well as the lipoprotein transport mechanisms.